The impact of the United Nations human rights treaties on the domestic level twenty years on - Heyns, C. H. (Christof H.); Viljoen, Frans; Murray, Rachel (Rachel H.) (Brill; Nijhoff, 2024)
"This collection of chapters tracks and explains the impact of the nine core United Nations human rights treaties in 20 selected countries, four from each of the five UN regions. Researchers based in each of these countries were responsible for the chapters, in which they assess the influence of the treaties and treaty body recommendations on legislation, policies, court decisions and practices. By covering the 20 years between July 1999 and June 2019, this book updates a study done 20 years ago"--